Long-Term Outcomes of Mitral Valve Repair Versus Replacement in Patients with Ischemic Mitral Regurgitation: A Retrospective Propensity-Matched Analysis - Ismail M. Elnagar; Rawan Alghamdi; Murtadha H. Alawami; Ahmad Alshammari; Abdulmalik A. Almedimigh; Monirah A. Albabtain; Alaa AlGhamdi; Huda H. Ismail; Mostafa A. Shalaby; Khaled A. Alotaibi; Amr A. Arafat (Journal of Cardiovascular Development and Disease)
Background: The optimal surgical management of ischemic mitral regurgitation (IMR)—mitral valve repair (MVr) versus mitral valve replacement (MVR)—remains controversial, with limited evidence on long-term outcomes. This study aimed to compare the outcomes of MVr and MVR in patients with IMR, focusing on survival and recurrence of mitral regurgitation. Additionally, survival was compared based on preoperative characteristics. Methods: A retrospective cohort analysis was conducted at a tertiary referral center and included 759 patients who underwent surgery for IMR between 2009 and 2021. Propensity score matching identified 140 matched pairs. The outcomes assessed included hospital mortality, long-term survival, recurrence of mitral regurgitation, mitral valve reintervention rates, and echocardiographic changes over time. Results: In the matched cohort, no significant differences were observed in hospital mortality (10% for MVr vs. 10.7% for MVR, p > 0.99) or long-term survival (p = 0.534). However, MVr was associated with a higher rate of recurrent moderate or higher mitral regurgitation (29.04% vs. 10.37%, p < 0.001) compared to MVR. The mitral valve reintervention rates did not differ significantly between the groups. Echocardiographic follow-up revealed significant improvements in left ventricular function and dimensions, with no significant differences between the groups. A subgroup analysis revealed no difference in survival according to the age, gender, ejection fraction, EuroSCORE category, or right ventricular function between the MVr and MVR patients. Conclusions: MVr and MVR for IMR yielded comparable survival rates, but MVr was associated with a higher risk of recurrent MR. The efficacy of both surgical approaches across diverse patient populations was comparable, reinforcing the need for individualized decision-making based on other clinical and anatomical considerations.